THE IMPLEMENTATION OF 5E LEARNING CYCLE MODEL ON THE TOPIC ‘STRUCTURE AND FUNCTION OF PLANTS’ TO IMPROVE THE SCIENTIFIC LITERACY OF THE SECOND YEAR STUDENTS OF A JUNIOR HIGH SCHOOL IN PEKANBARU - Evi Suryawati; Mariani Natalina; Nadia Nadia; Deswati Deswati (International Journal of Educational Best Practices, 2018)
Abstract: This study aims to improve student’s science literacy skills by using 5E Learning Cycle model. The treatment was conducted collaboratively for the topic ‘Structures and functions of plants’ involving Biology lectures, pre-service teachers, and the science school teachers of SMPN 21 Pekanbaru in August 2018. The focus of the observation was on science literacy and learning activities of students, both individually and in groups. Science literacy including scientific, procedural and epistemic knowledge was measured through worksheets. While the aspects of explaining scientific phenomena, evaluating and design scientific investigations, interpreting data, and the evidence were measured using an assessment sheet performance. Curiosity, scientific argumentation and environmental awareness were measured using the observation sheet. Learning activities carried out inside and outside the classroom had a positive impact on literacy skill science. The data showed the students individually or in groups could answer questions in the worksheet, more actively engaged, more enthusiastic and more curious when observing, identifying and grouping plants using real objects around school environment. Some questions arose from students when identifying corn and carrot plants about vegetative and generative structures. Overall, the implementation of 5E Learning Cycle model can improve students' scientific literacy in learning science at SMPN 21 Pekanbaru